2022
DOI: 10.3389/fonc.2022.1046630
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metabolic cancer therapy on tumor microenvironment

Abstract: Targeting tumor metabolism for cancer therapy is an old strategy. In fact, historically the first effective cancer therapeutics were directed at nucleotide metabolism. The spectrum of metabolic drugs considered in cancer increases rapidly – clinical trials are in progress for agents directed at glycolysis, oxidative phosphorylation, glutaminolysis and several others. These pathways are essential for cancer cell proliferation and redox homeostasis, but are also required, to various degrees, in other cell types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 242 publications
0
15
0
Order By: Relevance
“…The TME refers to the cellular environment in which the tumor exists ( 56 ). Numerous studies have confirmed that TME plays an important role in tumor development, adaptation, and pathogenesis ( 57 - 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…The TME refers to the cellular environment in which the tumor exists ( 56 ). Numerous studies have confirmed that TME plays an important role in tumor development, adaptation, and pathogenesis ( 57 - 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…114 Asparagine is one non-essential amino acid that can be targeted by the enzymeLasparaginase to decrease blood asparagine levels. 114 Currently,L-asparaginase is clinically approved for the treatment of some lymphomas and is undergoing clinical trials for solid tumors and other cancers. Currently, L-asparaginase is critical for achieving a high cure rate in pediatric acute lymphoblastic leukemia and is because the lymphoblasts lack asparagine synthase.…”
Section: Amino Acidmentioning
confidence: 99%
“…Additionally, other cells, such as endothelial cells and immune cells, use extracellular asparagine, the depletion of asparagine can have complex outcomes, including impaired immune response. 114,115 To overcome these issues, research is being conducted to develop novel drug combinations and L-asparaginase formulations. 115 The physiological function of tissue and disease is closely related to the spatial and temporal distribution of metabolites, and, understanding this, will allow a deeper understanding of disease state and phenotype.…”
Section: Amino Acidmentioning
confidence: 99%
See 2 more Smart Citations